PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEGAK BERSAMBUNG KELAS II SDIT SYIFAURRAHMAH - Riska Rudini Siregar; Sapri Sapri; Andina Halimsyah Rambe (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
The research that has been carried out is entitled "Development of Student Worksheets to Improve Continuous Continuous Writing Skills for Class II SDIT SYIFAURRAHMAH" which is based on the fact that student learning outcomes in Indonesian Language subjects can be obtained through continuous relationships, starting from learning to listen, then speaking, followed by learning to read, and finally writing. The research objectives are the validity, practicality and effectiveness of knowing LKPD in improving cursive writing skills in class II students. Can evaluate the practicality of LKPD in supporting the improvement of cursive writing skills. There is an assessment of the effectiveness of LKPD in developing cursive writing skills in class II students at SDIT SYIFAURRAHMAH. The research methodology uses the Research and Development (R&D) model method which uses the ADDIE model which aims to develop research products. Analysis, design, development, implementation, evaluation. The research population was Class II students at SDIT SYIFAURRAHMAH with a total of 30 students. The sampling technique was based on criteria set by the researcher. Data collection techniques using interviews, digital visual recordings carried out verbally and face to face by researchers. The research results reveal that based on the validation of the LKPD, it shows that the LKPD has a validity of 90%, feasibility of 95%, and design validity of 92%, all of which are in the high category. The practicality of the LKPD was assessed as very simple by teachers (90.2%) and students (89.2%). Effectiveness is considered quite effective with an NGain of 71.2%. The combination of validity, practicality and effectiveness factors shows that this worksheet is suitable for use as a teaching tool to develop cursive writing skills.